Built Environment Upgrading Recommendation for Slum Settlement in Pelambuan, Kuin Cerucuk, and Teluk Dalam District - Hanny Maria Caesarina; Aziza Rachmania; Stefani Azzahrah (UrbanGreen Central Media, 2022)
Slum area has been a serious matter to any city in the world. Banjarmasin has been struggling to minimize the percentage of its slum area. Some of it are located in Pelambuan, Kuin Cerucuk and Teluk Dalam districts. This community service intended to give an understanding regarding recommendation concept to revitalize slum area in those districts through series of community assistance. The method used was a combination of community education and dialogue focused on building quality improvement. The target group were people of Pelambuan, Kuin Cerucuk and Teluk Dalam district. Results show that the community agreed to control the land intensity of the area based on building base coefficient of 60-80%, as well as maintaining open space below their house for river flow.